Analysis of Regional Potency and Local Feed Resources to Develop Native Chicken in East Java Province - Didik Nur Edi (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2020)
This study aimed to depict the distribution of potential district/city in East Java Province to develop native chicken based on analysis of regional potency and local feed resources. The results of this investigation will provide preliminary information and a general overview of the direction of native chicken development in East Java Province. The methods used were location quotient analysis, population growth analysis, and local feed potency using secondary data from the BPS-Statistics of East Java Province 2015-2019. The data were analyzed descriptively. The results showed that there were 12 districts (Trenggalek, Jember, Banyuwangi, Bondowoso, Situbondo, Probolinggo, Sidoarjo, Nganjuk, Ngawi, Bojonegoro, Bangkalan, and Sumenep) and one city (Probolinggo) in East Java Province that potentially developed native chicken. This determination is because those regions being the basis of native chicken based on location quotient analysis, the population growth is always positive from 2015-2019, and had abundant local feed resources.